(untitled) (Indian Journal of Animal Production and Management, 2024)
Thirty two crossbred calves (16 each from Holstein Friesian and Jersey crossbred) at one week of age, with equal number of male and female were divided into four groups such as Group-1 (fed no molasses), Group-2 (20gm/ kg calf starter), Group-3 (40gm/ kg calf starter) and Group-4 (60gm/ kg calf starter). Calf starter (CP- 21% and TDN-75%) composed of crushed maize, wheat bran, rice polish, ground nut cake, mustard oil cake, skimmed milk powder, mineral mixture and common salts @ 44, 12, 10, 25, 5, 1, 2 and 1 percent respectively. Antibiotic powder Lixen (Cephalexin oral powder) was mixed with calf starter @ 20gm/ 100 kg of feed. Recording of physiological parameters such as rectal temperature (RT), pulse rate (PR) and respiration rate (RR) was done early morning at 8:30 am at fortnight interval from 7th to 97th day of age. Overall average RR, PR and RT did not differ statistically with respect to breeds and treatment. However, there was significant (p < 0.01) difference of overall RT due to sex and age. The overall average RT of female calves was significantly higher (102.26 ± 0.06 0F) than the male calves (101.85 ± 0.06 0F). In respect of age it was significantly lower on 97th day old calves (101.81 ± 0.14 0F). The overall average PR differed significantly (p<0.01) due to age and sex (p<0.05) and RR differed significantly (p<0.01) due to age only. The overall average PR minute was significantly higher in female (83.63 ± 0.24) than the male calves (83.16 ± 0.21). Both PR and RR per minute were observed to be gradually declined with advancement of age with significantly lower average on 97th day of age (80.69 ± 0.48 and 23.47 ± 0.24, respectively).